The Role of Ideology in Shaping Interests: A Marxist study on Pakistan’s Elite Class - Sahito, Muhammad Shahban; Pasha, Muhammad Ali; Noonari, Imran Ali (Annals of Human and Social Sciences, 2023)
This research study examine the influential role of ideology in determining the priorities of Pakistan’s ruling elite from a Marxist standpoint. Based on a comprehensive analysis of existing literature, this paper examines how ideology is utilized by the governing class as a means to advance their own interests. The study examines the composition of Pakistan’s ruling elite and highlights their substantial effect on the country’s political, economic, and social systems. The allegations of manipulating ideology for personal benefit rather than the collective well-being are subject to thorough scrutiny. Moreover, the study uncovers the extensive influence of these ideological pursuits on Pakistani society, specifically in intensifying economic disparity, social fragmentation, and political strife. The research illustrates that the utilization of ideology by ruling elites to strengthen their authority is not exclusive to Pakistan, as evidenced by international comparisons. The findings provide a basis for comprehending the intricate dynamics of power and ideology within the socio-political terrain of Pakistan.